Analysis of Senior High School Students’ Misconceptions on Chemical Bonding Using a Three-Tier Diagnostic Test - Nur Hairami Idrus; Masrid Pikoli; Erga Kurniawati; Julhim S. Tangio; Mangara Sihaloho; Thayban Thayban; Arviani Arviani; Siti Istiqomah Nggole (Universitas Negeri Gorontalo, 2026)
This study aims to identify the forms and levels of students’ misconceptions on chemical bonding concepts among Grade XI students at MAN 1 Gorontalo City. The research employed a descriptive quantitative approach using a three-tier diagnostic multiple-choice test consisting of 15 items covering the subtopics of basic chemical bonding concepts, ionic bonding, covalent bonding, metallic bonding, Lewis structures, and intermolecular forces. The participants were 72 Grade XI students who had previously studied chemical bonding. Students’ responses were analyzed based on the combination of answers, reasoning, and confidence levels, and then categorized into five conceptual categories: understanding the concept (PK), misconception type 1 (MK1), misconception type 2 (MK2), misconception type 3 (MK3), and lack of concept understanding (TPK). The results show that students’ overall conceptual understanding was relatively high at 82.78%, while the overall level of misconceptions reached 12.97%. The highest misconception was found in the basic concept of chemical bonding (17.36%), followed by ionic bonding (9.72%), covalent bonding (6.48%), intermolecular forces (6.60%), Lewis structures (4.17%), and metallic bonding (3.47%). Among the misconception categories, MK1 was the most dominant (7.50%), followed by MK3 (3.06%) and MK2 (2.41%). These findings indicate that although most students demonstrate a good level of conceptual understanding, misconceptions remain present in several subtopics of chemical bonding. Therefore, instructional strategies that emphasize conceptual clarification and multiple chemical representations are needed to improve students’ understanding of chemical bonding concepts.